Living Hadis di Era Digital: Media Sosial dan Transformasi Otoritas - Hazra Ria Habibah Dalimunthe; Nawir Yuslem; Ardiansyah Ardiansyah (Student Scientific Creativity Journal, 2026)
This study is motivated by the rapid proliferation of hadith dissemination in the digital era, which has significantly transformed patterns of transmission, religious authority, and public understanding. Social media has become a primary space for circulating hadith, often without adequate scholarly verification. Therefore, this study aims to analyze the dynamics of Living Hadith in the digital age, particularly focusing on hadith circulation, the shift of religious authority, and the challenges of hadith literacy in contemporary society. This research employs a qualitative approach using library research supported by digital document analysis from various social media platforms. Data were collected through literature review and documentation of digital content, and analyzed using content analysis and descriptive-analytical methods. The findings reveal an epistemological transformation in the practice of Living Hadith, where hadith not only exists in social practices but also operates within digital logic shaped by algorithms, popularity, and virality. Furthermore, there is a noticeable shift in religious authority from scholarly-based legitimacy to visibility-based influence. In conclusion, this study emphasizes the urgency of strengthening critical, hermeneutic, and digital hadith literacy to preserve the validity of hadith understanding in the post-truth era.